FACTORS ASSOCIATED WITH THE INCIDENCE OF DIABETES MELLITUS (DM) IN THE WORKING AREA OF UPTD PUSKESMAS LAGEUN, SETIA BAKTI DISTRICT, ACEH JAYA REGENCY, 2023/2024 - Khairumman, Khairumman; Amin, Muslim; Nurhaliza, Nurhaliza (Transpublika Publisher, 2024)
The objective of this study is to ascertain the factors associated with the occurrence of diabetes mellitus in the Loyat Bakti sub-district, Aceh Jaya district, in the year 2024. The methodology employed is a quantitative analytical approach, utilizing a cross-sectional design. The study population encompasses all individuals afflicted with diabetes mellitus within the catchment area of the UPTD Puskesmas Lageun, Loyat Bakti sub-district, Aceh Jaya district. Primary data constitutes the basis for this research, acquired through the distribution of questionnaires among respondents. The majority of the sample panel comprises 50 respondents, of which 40 are female and 11 are male, representing a vulnerable group. The age distribution of most respondents falls within the elderly range of 46-74 years, accounting for 92.2% of the total. Analysis of the relationship between physical activity and Body Mass Index (BMI) reveals that the majority of respondents have an ideal BMI, comprising 26 individuals engaged in physical activity and 10 individuals within the sedentary category, totaling 36 respondents. Conversely, within the non-ideal BMI group, 7 respondents are physically active, while none are sedentary, summing up to 7 respondents. Additionally, among those classified as having an obese BMI, 7 individuals are physically active, with 1 person being sedentary, yielding a total of 8 respondents. Overall, the association between physical activity and BMI comprises 40 active individuals and 11 sedentary respondents, totaling 51 participants.